2016
DOI: 10.1002/cjce.22428
|View full text |Cite
|
Sign up to set email alerts
|

Partial oxidation of methane to syngas over Pt/Rh/MgO catalyst supported on FeCralloy woven fibre

Abstract: Integrating a high-pressure syngas step with Fischer-Tropsch synthesis (FT) in a single vessel reduces investment and operating costs for Gas-toLiquids technology (GtL). Methane catalytic partial oxidation (CPOX) to produce syngas for FT is an economic opportunity for micro-refineries. Many metals and metal oxides selectively convert natural gas to CO and H 2 , but they also form coke, which must be removed intermittently, otherwise it deactivates the catalyst and can foul the reactor and process lines. Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 39 publications
(56 reference statements)
0
17
0
Order By: Relevance
“…Fig. 4 indicates that the reduced catalyst sample works stable with a high conversion of CH 4 and selectivity of the desired products, starting from 600 K. However, the unreduced catalyst starts work only at 923 K with 25.0 % conversion of CH 4 This demonstrates that the process runs with high selectivity in accordance with the reaction stoichiometry of SCO of CH 4 to synthesis gas, namely, CH 4 + 1 /2O 2 CO+2H 2 , at the optimum ratio of the initial reaction mixture CH 4 :O 2 = 2.0:1.0, T = 1173 K, GHSV = 9 10 5 h -1 , t = 0.004 s. The SCO of CH 4 to synthesis gas on 1.0 % Pt-, Ru-, and Pt-Ru supported on In this case, the high selectivity by H 2 (78.1-99.0 %) is maintained. The selectivity by CO is increased from 80.0 % to 99.0 % with reducing the contact time from 5.7 10 -3 to 3.4 10 -3 s, reaching 99.0 %, and then slowly declines to 63.39 % when t = 2.3 10 -3 s. When reducing the contact time from 5.7 10 -3 to 2.3 10 -3 s, the H 2 :CO ratio is increased from 2.12 to 2.46.…”
Section: Catalytic Propertiesmentioning
confidence: 93%
See 4 more Smart Citations
“…Fig. 4 indicates that the reduced catalyst sample works stable with a high conversion of CH 4 and selectivity of the desired products, starting from 600 K. However, the unreduced catalyst starts work only at 923 K with 25.0 % conversion of CH 4 This demonstrates that the process runs with high selectivity in accordance with the reaction stoichiometry of SCO of CH 4 to synthesis gas, namely, CH 4 + 1 /2O 2 CO+2H 2 , at the optimum ratio of the initial reaction mixture CH 4 :O 2 = 2.0:1.0, T = 1173 K, GHSV = 9 10 5 h -1 , t = 0.004 s. The SCO of CH 4 to synthesis gas on 1.0 % Pt-, Ru-, and Pt-Ru supported on In this case, the high selectivity by H 2 (78.1-99.0 %) is maintained. The selectivity by CO is increased from 80.0 % to 99.0 % with reducing the contact time from 5.7 10 -3 to 3.4 10 -3 s, reaching 99.0 %, and then slowly declines to 63.39 % when t = 2.3 10 -3 s. When reducing the contact time from 5.7 10 -3 to 2.3 10 -3 s, the H 2 :CO ratio is increased from 2.12 to 2.46.…”
Section: Catalytic Propertiesmentioning
confidence: 93%
“…Information on the use of metal grids from the Pt, Pt/5 % Rh, Pt/10 % Rh, Pt/10 % Ir and Pd in the reaction of selective catalytic oxidation (SCO) of methane is available in literature. The studies were conducted at atmospheric pressure, 973-1373 K, and 0.21-0.33 10 -3 s contact time (t) 1) with an CH 4 +O 2 +Ar reaction mixture at varying of CH 4 :O 2 ratio. It was shown that 90 % selectivity (S) by CO was observed at 20 % conversion (X) of CH 4 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations